Dor durante o exame odontológico em crianças com história de hospitalização em unidade de terapia intensiva neonatal: estudo caso-controle - Mundim, Ana Paula (2013)
Hospitalization at Neonatal Intensive Care Units (NICU) is commonly related to many invasive and painful procedures. It has been reported that painful experiences in infancy can be associated with pain perception in the future. Little is known about the relation between the history of NICU care and children’s pain behavior during the dental exam. This study aimed to compare the occurrence of pain during the dental exam of children with/out history of previous admission to a NICU. This case-control study enrolled 42 children, 5.7±0.4 years-old, 24 girls, with (n=21) and without (n=21) history of NICU care, exploring other medical/dental features potentially related to this association. Children’s pain perception was evaluated by the Brazilian versions of two scales: the observational measure “Faces, Legs, Activity, Cry, Consolability (FLACC) Pain Assessment Tool”, and the self-report Faces Pain Scale–Revised (FPS-R)”. Data were analyzed by descriptive statistics, Chi-square (likelihood ratio) and Mann-Whitney tests. Findings showed that 5 children (23.8%) with history of NICU care showed pain during the dental exam (FLACC≥1), compared to none from the control group (P=0.006). Most of the 42 children (90.0%) did not perceived pain during the dental exam (FPS-R), with no difference between case and control groups (P=0.238). NICU children had more hospitalization later in childhood (81.0%) than the control group (25.0%, P<0.001). Groups did not differ regarding chronic diseases (P=0.141). History of dental pain, dental treatment experience and negative behavior at the dentist did not differ between the 5 children with FLACC≥1 and the others (P>0.05). It was concluded that children with history of NICU care present more pain during dental exam than those who did not have this experience.